Are self-stigma, quality of life, and clinical data interrelated in schizophrenia spectrum patients? A cross-sectional outpatient study - Holubová, Michaela; Prasko, Jan; Latalova, Klara; Ociskova, Marie; Grambal, Aleš; Kamaradova, Dana; Vrbova, Kristyna; Hruby, Radovan (Patient preference and adherence, 2016)
BACKGROUND: Current research attention has been moving toward the needs of patients and their consequences for the quality of life (QoL). Self-stigma is a maladaptive psychosocial phenomenon disturbing the QoL in a substantial number of psychiatric patients. In our study, we examined the relationship between demographic data, the severity of symptoms, self-stigma, and QoL in patients with schizophrenia spectrum disorder. METHODS: Probands who met International Classification of Diseases-10 criteria for schizophrenia spectrum disorder (schizophrenia, schizoaffective disorder, or delusional disorder) were recruited in the study. We studied the correlations between the QoL measured by the QoL Satisfaction and Enjoyment Questionnaire, self-stigma assessed by the Internalized Stigma of Mental Illness, and severity of the disorder measured by the objective and subjective Clinical Global Impression severity scales in this cross-sectional study. RESULTS: A total of 109 psychotic patients and 91 healthy controls participated in the study. Compared with the control group, there was a lower QoL and a higher score of self-stigmatization in psychotic patients. We found the correlation between an overall rating of self-stigmatization, duration of disorder, and QoL. The level of self-stigmatization correlated positively with total symptom severity score and negatively with the QoL. Multiple regression analysis revealed that the overall rating of objective symptom severity and the score of self-stigma were significantly associated with the QoL. CONCLUSION: Our study suggests a negative impact of self-stigma level on the QoL in patients suffering from schizophrenia spectrum disorders.